Measuring of Vibration-Damping Properties of Cast Iron - Kováčiková, Petra; Vavro, Ján; Vavro, Ján; Dubec, Andrej (Manufacturing Technology Journal, 2018)
Nowadays, ever increasing demands are being made on equipment and machine structures. This fact negatively affects their lifespan, reliability and security. Internal damping is caused by material malfunctions in the microstructure, thermoelastic effects, movement of dislocations or the effects of swirling currents. This paper deals with microstructure, chemical composition and mechanical properties of ductile iron. These data are required as input parameters for computational modeling and numerical analysis. The numerical part is focused on the modal analysis of the homogeneous beam sample by finite element method in the ADINA software environment.
Keywords: cast iron; finite element methods; microstructure; mechanical properties